Teachers’ Beliefs in Developing English Materials for Vocational Schools - Khosiyono, Banun Havifah Cahyo (JOLLT Journal of Languages and Language Teaching, 2021)
This report is part of a larger study concerning teachersâ€™ belief towards materials development and their effectiveness in professional development (PD) in Indonesia. This case study attempted to explore how the Indonesian teachersâ€™ beliefs towards materials development for vocational school students in Indonesia. Seven out of thirteen English teachers of vocational schools in Indonesia are involved in this project and were interviewed and observed. They are developing materials for vocational schools. Findings show that teachers believed that they had some considerations to check what has contained the textbook’s development. Their beliefs were influenced by some factors such as experience, needs, situation, studentsâ€™ interest, studentsâ€™ ability, workshop, and references. Also, the teachers’ deficient time and different views were two major problems faced by the teachers when conducting materials selection and analysisâ€”implications for how teachersâ€™ perception toward English materials development in vocational schools.